2020
DOI: 10.1177/0162643420962011
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Virtual Reality Intervention Research for Students With Disabilities in K–12 Settings

Abstract: Virtual reality (VR) technology has improved in access and availability in the area of K–12 instruction, increasingly being cited for its promise to meet the varied learning needs of individuals with disabilities. This descriptive review of 25 research studies conducted in K–12 settings examined the defining characteristics of immersion levels associated with VR, the purpose and application of the augmented reality intervention, the outcomes associated with the current use of VR, and the possibility of general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The objective of VR is to offer an authentic experience to users by placing them in a safe and controllable environment. The increasing affordability of IT applications is creating favorable conditions and offering increasing opportunities to use VR in educational processes [ 53 ], thus being able to respond to the different learning needs of people with disabilities [ 20 ]. Two attributes of VR can contribute to increasing the accessibility of the education process—“the sense of presence, and the embodied affordances of gesture and manipulation in the 3rd dimension” [ 54 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of VR is to offer an authentic experience to users by placing them in a safe and controllable environment. The increasing affordability of IT applications is creating favorable conditions and offering increasing opportunities to use VR in educational processes [ 53 ], thus being able to respond to the different learning needs of people with disabilities [ 20 ]. Two attributes of VR can contribute to increasing the accessibility of the education process—“the sense of presence, and the embodied affordances of gesture and manipulation in the 3rd dimension” [ 54 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Other studies revealed that children with disabilities, especially from Northern countries, are thought to be the main beneficiaries of this “digital revolution” [ 17 ]. Specialists claim that these children can benefit from appropriate learning materials and overcome communication barriers with the help of “cyber learning techniques and environments” [ 18 , 19 , 20 ]. According to UNICEF, at least 93 million children with disabilities “are one of the most marginalized and excluded groups in society and they suffer from discrimination with regard to access to education” [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Carreon and colleagues in their review (2022) indicated the necessity of affordances in Virtual Reality (VR) interventions for students with disabilities (Carreon et al, 2022). This was shown by the immersive qualities (which imply affordances) of VR and their contribution to building academic skills in various disciplines.…”
Section: Digital Technology In Science Education For Students With Di...mentioning
confidence: 99%
“…However, all these advantages of such technologies are often not considered. In their literature review, Carreon, Smith, Mosher, Rao and Rowland (2020) show that in K-12 settings VR is mostly used in non-immersive simulations that are shown on a screen. Yet it is these immersive features that make VR an especially appealing tool for learners with disabilities (ibid.…”
Section: Project Example Inclusive Peer Learning With Augmented Reali...mentioning
confidence: 99%